What matters in laparoscopic hepatectomy for lesions located in posterosuperior segments?: Initial experiences and analysis of risk factors for postoperative complications$da retrospective cohort study - Téoule, Patrick; Dunker, Niccolo; Gölz, Vanessa; Rasbach, Erik; Reißfelder, Christoph; Birgin, Emrullah; Rahbari, Nuh Nabi (Surgical endoscopy and other interventional techniques, 2025)
Background Laparoscopic liver resection (LLR) for lesions in the posterosuperior segments (PSS) is challenging. Identifying and minimizing risk factors for postoperative morbidity and mortality is crucial. This retrospective cohort study shares initial experiences with LLR of the PSS (VII, VIII, IVa) and wants to identify risk factors for clinically relevant postoperative complications (Clavien-Dindo grade ≥ III) in these patients. Methods We reviewed our prospective database for all patients who underwent LLR with at least one lesion in the PSS (April 2018-October 2022). Uni- and multivariate analyses were carried out using binary logistic regression analysis. Results 110 patients underwent LLR of the PSS. Median age was 67 years (IQR 59-76); 62% were male (n = 68), with a median BMI of 26 (IQR 23-30). The most frequent indications for LLR were primary liver cancer (37%) and colorectal liver metastasis (36%). Median operating time was 211 min (IQR 135-281) with a median blood loss of 460 mL (IQR 240-1200). Postoperative length of stay was 6 days (IQR 4-8). Clinically relevant postoperative complications were present in 20 patients (18%) with a 90-day mortality rate of 5% (n = 6). Multivariate analyses identified ASA ≥ III (OR 3.23 [95%CI 1.03-10.09]; p = 0.043), diabetes (OR 4.31 [95%CI 1.20-15.49]; p = 0.025), and intraoperative transfusion of packed red blood cells (PRBC) (OR 4.80 [95%CI 1.01-22.86]; p = 0.049) as risk factors for Clavien-Dindo grade ≥ III complications. Conclusion ASA ≥ III status, diabetes, and intraoperative PRBC transfusion are associated with an increased risk of Clavien-Dindo grade ≥ III complications in patients undergoing LLR in PSS. Preoperative optimization should include diabetes management, screening for anemia with appropriate supplementation, and comprehensive risk counseling for ASA ≥ III patients. Additionally, minimizing intraoperative PRBC transfusion should remain a key perioperative goal.
Online veröffentlicht: 30. April 2025
Gesehen am 01.07.2025